Construction of a superior visible-light-driven photocatalyst based on a C3N4 active centre-photoelectron shift platform-electron withdrawing unit triadic structure covalent organic framework. Issue 69 (15th August 2017) - He, Sijing; Rong, Qinfeng; Niu, Hongyun; Cai, Yaqi
Abstract : Through ingenious design of the molecular structure, we constructed a novel covalent organic framework as a visible-light photocatalyst with superior activity. Abstract : Herein, three functional factors inducing photocatalytic ability were artfully integrated into a covalent organic framework (COF), where triazine units served as photoactive centers, cyclic ketone units served as electron-withdrawing moieties, and the conjugated structure served as a photoelectron shift platform. This COF with segregated donor–acceptor alignments exhibits an excellent visible-light photocatalytic capacity for the decomposition of organic pollutants.